El estigma percibido por personas que viven con adicciones - Ceferino Piedra, James Isidro (My University, 2025)
This study explores the impact of perceived stigma on individuals with substance use disorders (SUD) through a qualitative approach and hermeneutic phenomenology. Various types of stigma (social, structural, and individual) are identified, along with their influence on access to resources, employment, and housing. Using semi-structured interviews with a convenience and snowball sampling method, testimonies were collected regarding discrimination in social settings, healthcare services, and work environments. Data analysis revealed four main categories: perception of social stigma, impact on mental health, family relationships, and coping strategies. Findings indicate that stigma leads to low self-esteem, social anxiety, and hopelessness, as well as family conflicts and conditional support. Regarding coping strategies, participants rely on support networks and self-acceptance, though significant barriers persist. The study concludes that stigma not only hinders recovery but also perpetuates social exclusion. It recommends the development of inclusive policies and intervention strategies to reduce discrimination and promote the social reintegration of individuals with SUD.
El estudio explora el impacto del estigma percibido en personas con trastornos por uso de sustancias (TUS) mediante un enfoque cualitativo y fenomenología hermenéutica. Se identifican distintos tipos de estigma (social, estructural e individual) y su influencia en el acceso a recursos, empleo y vivienda. A través de entrevistas semiestructuradas a una muestra por conveniencia y bola de nieve, se recolectaron testimonios sobre discriminación en espacios sociales, servicios de salud y entornos laborales. El análisis de datos reveló cuatro categorías principales: percepción del estigma social, impacto en la salud mental, relaciones familiares y estrategias de afrontamiento. Se observó que el estigma genera baja autoestima, ansiedad social y desesperanza, además de conflictos familiares y apoyo condicionado. En cuanto a las estrategias de afrontamiento, los participantes recurren a redes de apoyo y autoaceptación, aunque con barreras significativas. El estudio concluye que el estigma no solo dificulta la recuperación, sino que perpetúa la exclusión social. Se recomienda desarrollar políticas inclusivas y estrategias de intervención que reduzcan la discriminación y fomenten la reintegración social de personas con TUS.
Keywords: ESTIGMA PERCIBIDO; TRASTORNOS POR USO DE SUSTANCIAS; DISCRIMINACIÓN; EXCLUSIÓN SOCIAL